Peran Otak dalam Perkembangan dan Penggunaan Bahasa pada Manusia: Peran Otak dalam Perkembangan dan Penggunaan Bahasa pada Manusia - nur qodriyah safitri; Silvina Noviyanti; Diva Medika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study examines the role of the brain in the development and use of language in humans as the primary effective communication tool in forming harmonious social relationships. Using a systematic literature review method, the analysis focuses on the neurological functions of the left hemisphere, specifically the Broca's area for articulatory production and Wernicke's area for semantic comprehension, which are connected by the arcuate fasciculus, as well as the contribution of the right hemisphere to prosody and emotional context. The language process involves an integrated neural network in the cerebral cortex, working memory, sensory perception, and neuroplasticity that supports lifelong adaptation, including aphasia recovery. Neuroimaging findings such as fMRI confirm this real-time dynamic, opening implications for neurolinguistic teaching and rehabilitation strategies. Overall, language reflects a complex interaction among brain structures, genetic factors, the environment, and unique cognitive experiences in humans. Keywords: Role of the brain, Language development​, Wernicke's area